2001
DOI: 10.1302/0301-620x.83b3.11218
|View full text |Cite
|
Sign up to set email alerts
|

Fractures involving splitting of the humeral head

Abstract: Splitting fractures of the humeral head are rare; part of the humeral head dislocates and the unfractured part remains attached to the shaft. We report eight cases in young patients. In five the diagnosis was made at presentation: three had minimal internal fixation using a superior subacromial approach, one had a closed reduction and one a primary prosthetic replacement. All five patients regained excellent function with no avascular necrosis at two years. In three the injury was initially unrecognised; two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Patients presenting with head-split fractures generally can be divided into two groups. One group includes younger and predominantly male patients involved in high-energy trauma (i. e., bicycle, motorcycle-, or car accident; epileptic seizure) with typically good bone quality and good potential for revascularization [4]. The other group includes older mainly female patients involved in low-energy trauma (i. e., a simple fall) and typically poor bone quality with limited regenerative potential [9].…”
Section: Epidemiology and Mechanism Of Injurymentioning
confidence: 99%
See 3 more Smart Citations
“…Patients presenting with head-split fractures generally can be divided into two groups. One group includes younger and predominantly male patients involved in high-energy trauma (i. e., bicycle, motorcycle-, or car accident; epileptic seizure) with typically good bone quality and good potential for revascularization [4]. The other group includes older mainly female patients involved in low-energy trauma (i. e., a simple fall) and typically poor bone quality with limited regenerative potential [9].…”
Section: Epidemiology and Mechanism Of Injurymentioning
confidence: 99%
“…The number of fragments in the setting of severe comminution is underestimated by standard radiography in more than 60% of cases [10]. Chesser et al reported that head-split fractures in particular can be difficult to recognize, and, when left untreated, poor outcomes can be expected [4]. Greiwe et al reported that only 37.5% of the head-split fractures were identified on preoperative radiographs and 50% on CT [9].…”
Section: » Nondisplaced Head-split Fractures May Be Treated Conservatmentioning
confidence: 99%
See 2 more Smart Citations
“…Head-split fractures are rare (less than 5% of all proximal humerus fractures) and difficult to identify on injury radiographs. 13,14 The outcome of head-split fractures, regardless of management, is thought to be worse than nonhead-split fractures because of a perceived higher energy of injury and disruption of the terminal blood supply to the articular fragments. 14 Treatment for head-split fractures in older patients has typically been humeral head replacement due to the disruption of articular surface congruity and vascularity.…”
Section: A B E905mentioning
confidence: 99%